The Digital Madrasah as an Idea of IT-Based Islamic Education - Sedya Santosa; Muhammad Fahmi Jazuli (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
In this article, the author will review the opportunities for madrasah as Islamic educational institutions in facing modernization, as well as what learning methods are appropriate to use in learning. The term